Regulasi Kosmetik Terhadap Izin Edar: A Studi Literature - Dewi Rahmawati; Marcelinda Krisdivayanti; Icasia Carolina Dewi; Amelia Saputri Ginting; Tarizza Puspa Anggrelia; Herta Meidya Nurhalita; Laila Sabila Sindriyani; Rosa Virginia Tuda Kou; Kurrota Ayyun; Alfi Dwi Seviah; Nadiya Kamiliya Putri; Yeka Khafidz Ila Rosyidah (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Cosmetics have varied purposes, including cleansing, increasing brightness, changing appearance, and protecting or maintaining certain conditions. The applicable cosmetics regulations are explained in the BPOM provisions, which mandate registration before cosmetics can be used by consumers. In this research, the results of two literature reviews are presented that support this statement. The first study by (Chandra Adi Gunawan Putra, 2023) shows that the need for state involvement in protecting consumers arises because of the power imbalance between business actors and consumers. The second study by (Ribka Amanda Dera, 2019) the regulation of cosmetic products has been regulated by BPOM number 12 of 2020 article 2 paragraph 1 which emphasizes that cosmetics producers must ensure that their products which will be distributed both domestically and abroad meet the criteria, safety and security standards. benefits, quality marking, and claims. The results of both studies show that the importance of terms and conditions related to cosmetics are under law and regulated in the Republic of Indonesia Constitution, the Health Law, provisions issued by the Minister of Health and decisions taken by the Head of the Republic of Indonesia Food and Drug Supervisory Agency and in BPOM regulations starting from formulation to product withdrawal. So that any party who commits an illegal act by producing or distributing pharmaceutical or cosmetic products without a permit will receive applicable sanctions in accordance with legal provisions.